2015
DOI: 10.4064/fm231-3-4
|View full text |Cite
|
Sign up to set email alerts
|

On Borel reducibility in generalized Baire space

Abstract: We show that although the Galvin-Prikry Theorem does not hold on generalized Baire space with the standard topol-ogy, there are similar theorems which do hold on generalized Baire space with certain coarser topologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…If the answer is “yes”, then a partial answer to Question is obtained (cf. ): if T 1 is classifiable and shallow, T 2 is non‐classifiable and κ=λ+=2λ>2ω where λ<λ=λ, then (T1κ)normalB(T2κ).…”
Section: The List Of Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the answer is “yes”, then a partial answer to Question is obtained (cf. ): if T 1 is classifiable and shallow, T 2 is non‐classifiable and κ=λ+=2λ>2ω where λ<λ=λ, then (T1κ)normalB(T2κ).…”
Section: The List Of Open Questionsmentioning
confidence: 99%
“…Further background. If the answer is "yes", then a partial answer to Question 3.45 is obtained (cf [23]…”
mentioning
confidence: 99%
“…It was asked in Friedman, Hyttinen, and Kulikov [3] and in Khomskii, Laguzzi, Löwe, and Sharankou [8,Question 3.46] whether or not the equivalence relation modulo the nonstationary ideal on the Baire space can be reduced to the Cantor space for some fixed cofinality: in our notation, whether or not E Ä;Ä S Ä Ä E 2;Ä S Ä . We approach the problem by proving several results in this direction.…”
Section: Theorem 12 ([2 Theorem 55])mentioning
confidence: 99%
“…In , the relation Eμ- club λ, 1<λκ, has been studied on the closed subspaces λκ, with λ<κ and the relative subspace topology. The relation Eμ- club λ on the subspace λκ is defined as: we say that f,gλκ are Eμ- club λ equivalent (fEμ- club λg) if the set {α<κ;f(α)=g(α)} contains a μ‐club.…”
Section: Stable Unsuperstable Theoriesmentioning
confidence: 99%
“…Also it was shown that if a theory T has this property and V=L, then T is Σ11‐complete. Finally, by combining [, Corollary 15] and the proof of [, Theorem 16], it follows that if T is classifiable and shallow, then T is reducible to Tω+ω.…”
Section: Introductionmentioning
confidence: 98%